2016
DOI: 10.7883/yoken.jjid.2015.062
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Genetic Diversity among Invasive <i>Streptococcus pneumoniae</i> Isolates in Turkey

Abstract: SUMMARY: This study obtained information on the serotypes and molecular typing characteristics of Streptococcus pneumoniae strains causing invasive diseases in Turkey. Sixty-eight S. pneumoniae isolates causing invasive pneumococcal diseases were collected from different regions of Turkey from 2009 to 2011. The isolates were characterized by performing multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), and capsular serotyping, and 25 different serotypes were identified. Serotypes 19F, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Penicillin non-susceptible isolates in Turkey, North America, and Europe were 19.1%, 9% -24%, and 0% -43%, respectively (20). In previous studies from Iran, the antibiotic susceptibility profile has been different and it has been totally shown that resistance to erythromycin, cefotaxime, cotrimoxazole, chloramphenicol, and penicillin is increasing (21,22).…”
Section: Discussionmentioning
confidence: 97%
“…Penicillin non-susceptible isolates in Turkey, North America, and Europe were 19.1%, 9% -24%, and 0% -43%, respectively (20). In previous studies from Iran, the antibiotic susceptibility profile has been different and it has been totally shown that resistance to erythromycin, cefotaxime, cotrimoxazole, chloramphenicol, and penicillin is increasing (21,22).…”
Section: Discussionmentioning
confidence: 97%
“…Increasing incidence of PNSP has become a worldwide problem since the 1980s [16], [17] and has created severe problems regarding the management of IPD [1]. The prevalence of PNSP in Asian countries varies widely [5], [18], [19]. The rapid growth in incidence may result from the intercontinental spread of a few PNSP clones [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, in Skåne, the prevalence of PNSP increased from 8% to 10% [23], [24]. Non-susceptible isolates were reported from Turkey (19.1%), North America (9%–24%) and Europe (0%–43%) [18], [25]. In recent studies from the USA (2011) and Asian countries (2012) prevalences were 14.8% and 4.8%, respectively [23].…”
Section: Discussionmentioning
confidence: 99%
“…Isolates of hyperinvasive clones are constantly circulating and are able to modify their phenotypic profile (e.g. in Turkey, prevalence of ST242 and ST230 in serotype 14, with emerging resistance to penicillin was observed [68,69]. Also, variants of ST230 clone were identified in serotypes 19A, 19F, and 7F [69]).…”
Section: Vaccine Pressure On Serotype Replacement and Resistance Of Isolatesmentioning
confidence: 99%